Palliation, end-of-life care and burns; concepts, decision-making and communication – A narrative review - Daan den Hollander (African Journal of Emergency Medicine, 2020)
Palliative care is the turn from cure as the priority of care to symptom relief and comfort care. Although very little is published in the burn literature on palliative care, guidelines can be gleaned from the general literature on palliative care, particularly for acute surgical and critical care patients. Palliative care may be started because of futility, on request of the patient, or because of limited resources. The SPIKES acronym is a useful guide to avoid errors in communication with terminal patients and their relatives.